Compositional MRI of the Hip: Reproducibility, Effect of Joint Unloading, and Comparison of T2 Relaxometry with Delayed Gadolinium-Enhanced Magnetic Resonance Imaging of Cartilage. (October 2021) - Fernquest, Scott; Palmer, Antony; Gammer, Bonnie; Hirons, Emma; Kendrick, Benjamin; Taylor, Adrian; De Berker, Henry; Bangerter, Neal; Carr, Andrew; Glyn-Jones, Sion
Objective: Our aim was to compare T2 with delayed gadolinium-enhanced magnetic resonance imaging of cartilage (dGEMRIC) in the hip and assess the reproducibility and effect of joint unloading on T2 mapping. Design: Ten individuals at high risk of developing hip osteoarthritis (SibKids) underwent contemporaneous T2 mapping and dGEMRIC in the hip (10 hips). Twelve healthy volunteers underwent T2 mapping of both hips (24 hips) at time points 25, 35, 45, and 55 minutes post offloading. Acetabular and femoral cartilage was manually segmented into regions of interest. The relationship between T2 and dGEMRIC values from anatomically corresponding regions of interests was quantified using Pearson's correlation. The reproducibility of image analysis for T2 and dGEMRIC, and reproducibility of image acquisition for T2, was quantified using the intraclass correlation coefficient (ICC), root mean square coefficient of variance (RMSCoV), smallest detectable difference (SDD), and Bland-Altman plots. The paired t test was used to determine if difference existed in T2 values at different unloading times. Results: T2 values correlated most strongly with dGEMRIC values in diseased cartilage ( r = −0.61, P = <0.001). T2 image analysis (segmentation) reproducibility was ICC = 0.96 to 0.98, RMSCoV = 3.5% to 5.2%, and SDD = 2.2 to 3.5 ms. T2 values at 25 minutes unloading were not significantly different to longer unloading times ( P = 0.132). SDD for T2 image acquisition reproducibility was 7.1 to 7.4 ms. Conclusions: T2 values in the hip correlate well with dGEMRIC in areas of cartilage damage. T2 shows high reproducibility and values do not change beyond 25 minutes of joint unloading.